Decolonization, with or without the Mother Tongue: The Blinkards - Jeyifo, Biodun (Research in African literatures, 2025)
The article develops the idea of an uncolonizable language as a language that belongs to all. This analysis contrasts Frantz Fanon's theorization of colonized societies in which the ideas of the mother tongue, indigenous cultural resources, and the struggle for self-representation are much less salient, with critiques developed by other postcolonial and post-classical theorists and thinkers like Ngugi wa Thiong'o, Amilcar Cabral, Audre Lorde, Sylvia Wynter, Edouard Glissant, or Abiola Irele. To illustrate this argument, a reading of Kobina Sekyi's The Blinkards and Brian Friel's Translations asks readers to consider the racialization of English as the "language of whites" through the lens of colonial catachresis.